2014
DOI: 10.1007/s00405-014-3368-9
|View full text |Cite
|
Sign up to set email alerts
|

CO2 laser cordectomy for glottic squamous cell carcinoma involving the anterior commissure: voice and oncologic outcomes

Abstract: Transoral CO2 laser cordectomy for squamous cell carcinoma (SCC) of the glottis has resulted in excellent voice and oncologic outcomes as compared with non-surgical therapy. However, published experience with primary CO2 laser cordectomy specifically for glottic SCC involving the anterior commissure (AC) is limited. A review of single academic institution experience with CO2 laser cordectomy for glottic SCC involving the AC. Patients undergoing European Laryngological Society (ELS) classification cordectomy ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 17 publications
(24 reference statements)
6
24
1
Order By: Relevance
“…The inclusion criteria for TLM of T3 laryngeal cancer applied in the present series are relatively more restrictive compared to those of other authors . From our point of view, in fact, a reasonable and radical control of the disease by a transoral approach cannot be achieved when the lesion involves the laryngeal framework and/or tends to grow outside the laryngeal box . In fact, the anterior encroachment of the thyroid cartilage or thyrohyoid membrane makes the tumor at risk of persistence after TLM even when part of the thyroid cartilage or prelaryngeal muscles are removed from the inside.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The inclusion criteria for TLM of T3 laryngeal cancer applied in the present series are relatively more restrictive compared to those of other authors . From our point of view, in fact, a reasonable and radical control of the disease by a transoral approach cannot be achieved when the lesion involves the laryngeal framework and/or tends to grow outside the laryngeal box . In fact, the anterior encroachment of the thyroid cartilage or thyrohyoid membrane makes the tumor at risk of persistence after TLM even when part of the thyroid cartilage or prelaryngeal muscles are removed from the inside.…”
Section: Discussionmentioning
confidence: 81%
“…In fact, the anterior encroachment of the thyroid cartilage or thyrohyoid membrane makes the tumor at risk of persistence after TLM even when part of the thyroid cartilage or prelaryngeal muscles are removed from the inside. Apart the technical difficulties, the biological behavior of such a lesion becomes definitely unpredictable and not manageable with this approach because the medullary spread of the tumor within the thyroid cartilage is not amenable to intraoperative visual or histopathological confirmation . The same holds true for the pathway of diffusion into the posterior paraglottic space, where the tumor reaches the cricoarytenoid joint and adjacent muscles, recurrent nerve and branches of the inferior laryngeal artery, and piriform sinus.…”
Section: Discussionmentioning
confidence: 99%
“…The significant correlations of Grade with other parameters at the late postoperative period (>6 months) implied that improvement in Grade, which represents overall voice quality on the GRBAS scale, might be considered probable improvement in quality of voice after TLM. Although there may be some controversy over considering the result of the GRBAS scale or VHI as a verification method for voice quality after TLM, several authors have demonstrated that these methods reflect postoperative vocal outcomes . On the other hand, quantitative acoustic measurement using the scales of the CSL–MDVP should be analyzed with caution because they are based on analysis of simple vowel phonation.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors argue this to be a weak point where tumor easily penetrates the cartilage transforming a T1 tumor into a T4 [43, 61]. Conversely, others have emphasized that Broyles’ ligament protects the cartilage and that therefore, tumors with superficial extension in the AC, especially in the horizontal plane (T1), rarely show thyroid cartilage infiltration [29, 62, 63]. This is in line with the author’s own experience where a past inventory at our institution of T1 tumors with anterior commissure involvement did not reveal any cases of hidden cartilage invasion (unpublished data).…”
Section: Factors Affecting Oncological Outcomes Of Tlmmentioning
confidence: 99%
“…Mendelsohn found a postoperative VHI of 24 in 13 patients undergoing extended resections (type III–VI) with a mean grade of 2 (moderate dysphonia) [102]. The same author also published one of the only reports specifically on voice outcome after resections of the AC which showed a VHI of 37 and a mean grade of 2.1 (moderate dysphonia) in these patients [63]. Peretti reported on 89 type V resections (59 T2 and 30 T3 carcinomas).…”
Section: Functional Outcomes Of Tlmmentioning
confidence: 99%